Comparison of the neural correlates of encoding item-item and item-context associations - Wong, Jenny X.; de Chastelaine, Marianne; Rugg, Michael D. (Frontiers in Human Neuroscience, 2013)
fMRI was employed to investigate the role of the left inferior frontal gyrus (LIFG) in the encoding of item-item and item-context associations. On each of a series of study trials subjects viewed a picture that was presented either to the left or right of fixation, along with a subsequently presented word that appeared at fixation. Memory was tested in a subsequent memory test that took place outside of the scanner. On each test trial one of two forced choice judgments was required. For the associative test, subjects chose between the word paired with the picture at study and a word studied on a different trial. For the source test, the judgment was whether the picture had been presented on the left or right. Successful encoding of associative information was accompanied by subsequent memory effects in several cortical regions, including much of the LIFG. By contrast, successful source encoding was selectively associated with a subsequent memory effect in right fusiform cortex. The finding that the LIFG was enhanced during successful associative, but not source, encoding is interpreted in light of the proposal that subsequent memory effects are localized to cortical regions engaged by the on-line demands of the study task.